2015
DOI: 10.1093/nar/gkv083
|View full text |Cite
|
Sign up to set email alerts
|

bHLH proteins involved in Drosophila neurogenesis are mutually regulated at the level of stability

Abstract: Proneural bHLH activators are expressed in all neuroectodermal regions prefiguring events of central and peripheral neurogenesis. Drosophila Sc is a prototypical proneural activator that heterodimerizes with the E-protein Daughterless (Da) and is antagonized by, among others, the E(spl) repressors. We determined parameters that regulate Sc stability in Drosophila S2 cells. We found that Sc is a very labile phosphoprotein and its turnover takes place via at least three proteasome-dependent mechanisms. (i) When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 96 publications
2
23
0
Order By: Relevance
“…1C ), and then declined rapidly in differentiation medium to the point where it was undetectable by d13 (9 days in differentiation media). This is consistent with previous studies suggesting that Ascl1 protein levels are tightly regulated in co-ordination with neurogenesis 11 , 19 . As bHLH transcription factors are known to be regulated at the level of protein half-life, we next examined whether Ascl1 protein stability differs as NSCs progress through the differentiation programme, determining protein abundance after the addition of cycloheximide to block ongoing protein synthesis.…”
Section: Resultssupporting
confidence: 94%
“…1C ), and then declined rapidly in differentiation medium to the point where it was undetectable by d13 (9 days in differentiation media). This is consistent with previous studies suggesting that Ascl1 protein levels are tightly regulated in co-ordination with neurogenesis 11 , 19 . As bHLH transcription factors are known to be regulated at the level of protein half-life, we next examined whether Ascl1 protein stability differs as NSCs progress through the differentiation programme, determining protein abundance after the addition of cycloheximide to block ongoing protein synthesis.…”
Section: Resultssupporting
confidence: 94%
“…Similar studies showed that Da itself was a stable protein ( Figure 3C,F ) although Da stability might be somewhat shortened by costransfection with Emc ( Figure 3D,F ). The half-life of Da alone was estimated at > 300 min, but that of Da co-transfected with Emc at 139 min ( Kiparaki et al, 2015 )( Figure 3D,F ). It would be interesting to investigate whether this difference affects Da levels in vivo when emc is mutated.…”
Section: Resultsmentioning
confidence: 99%
“…Some distinctions between proneural bHLH genes must be due to their interactions with other regulatory factors, which explains, for example, how genes such as ato and Atoh1 can be responsible for different neuronal cell types in distinct tissues (Kiefer et al, 2005;Huang et al, 2014). There is also increasing evidence that, in addition to transcriptional regulation, the regulation of bHLH protein stability is important (Qu et al, 2013;Kiparaki et al, 2015;Weinberger et al, 2017;Li and Baker, 2018). Also, genes under constraint by multiple mechanisms may behave less effectively in gene replacement experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking autoregulation in this way is an effective means of permanently extinguishing gene expression and might be exploited by Notch signaling in many situations (Baker, 2004). In addition, there is increasing evidence that Notch signaling affects proneural protein stability, which would also negatively impact autoregulation (Kiparaki et al, 2015;Weinberger et al, 2017).…”
Section: Drosophila Atonal As a Platform For Understanding Proneural mentioning
confidence: 99%